Sikap dan pengetahuan tentang kehamilan remaja di 3 SLTA Manado - Ongela, Franky (e-CliniC, 2014)
Abstrak: Teenage is one of unique life phase which characterized by change in social and biological; centralized on both healthy physical and psychological condition. Although, the understanding and expectation of being a teenage as a transition period between a child to a young adult are vary in social context. Teenage pregnancy may relate to negative outcome to parent, the child, and the society. Babies who are born by the result of teenage pregnancy will face a different life challenges. They most likely to suffer from education, attitude, and health in their life, compare to the babies who are born naturally when the parents are married in adequate age. There is several of contributing factor to unplanned pregnancy for teenagers. Such as pressure for married and having babies in young age, limited access to education and unemployment. The objectives of this research are to understand how the attitude and knowledge of teenagers towards the issue of `teenage pregnancy. This research is based on descriptive analyze with questionnaire method. The research of attitude and teenage knowledge about teenage pregnancy was conducted in three high schools in Manado City which are, SMA Rex Mundi (A), SMA 7 (B), and SMK 6 (C). The results shows the age of participating respondents are between 15-19 years old in each three schools and in order of percentage 91.7%, 83.3%, and 78.3% respectively. Parent’s education levels are respectively; 32% for father with degree, 61,7% for high school & 78,3%; and mother with degree for 50%, 68,3% for high school and 73,3% . For father occupation in private sector respectively 70%, 56,7% and 75%. For mother occupation in private sector respectively 48.3%, 68.3%, and 70%. The most source of information for the three schools are mass media and respectively in percentage; 23.3%, 26.4%, & 27.1%. The knowledge of pregnancy in the three schools is satisfactory level and respectively 70.0%, 76.7%, and 65%. The attitude of the three schools towards the issue is positive with percentage of 65%, 58.3% and 63.3 % respectively. With adequate knowledge about teenage pregnancy from this research, it provides a more positive attitude to avoid pregnancy in teen age. Keyword: Teenage, teenage pregnancy, knowledge, attitude Abstrak: Masa remaja sebagai suatu fase kehidupan yang berbeda yang dikarakteristik oleh penanda sosial dan biologi, pusat keadaan yang sehat fisik dan psikologis. Namun, pengertian dan ekspektasi dari remaja, sebagai suatu periode pertengahan antara anak-anak dan dewasa, bisa bervariasi dalam konteks sosial.Kehamilan masa remaja berhubungan dengan akibat negatif bagi orang tua, anak mereka dan masyarakat. Anak-anak yang lahir dari remaja akan menghadapi tantangan-tangangan khusus. Mereka mungkin akan menghadapi masalah dalam pendidikan, perilaku dan kesehatan sepanjang hidup mereka, dibandingkan dengan anak-anak yang lahir dari orang tua yang telah dewasa.Terdapat beberapa faktor yang berkontribusi terhadap kehamilan yang tidak direncanakan dan diinginkan pada remaja. Tekanan untuk menikah dan memiliki anak di usiadini, akses pendidikan yang terbatas dan tidak memiliki prospek pekerjaan, hal-hal tersebut membuat remaja akhirnya memilih untuk menikah. Tujuan penelitian ini untuk mengetahui, bagaimana sikap dan pengetahuan remaja terhadap kehamilan remaja. Penelitian ini bersifat analisa deskriptif dengan metode kuesioner. Penelitian sikap dan pengetahuan remaja tentang kehamilan remaja dilakukan pada 3 sekolah di Kota Manado, yaitu SMA Rex Mundi (A), SMA 7 (B) dan SMK 6 (C). Hasil yang diperoleh adalah: usia responden yang paling banyak berperan dalam penelitian ini adalah usia 15-19 tahun pada ketiga sekolah, beruturut-turut 91,7 %, 83,3 % dan 90,0 %. Tingkat pendidikan orang tuaberturut-turut; untuk ayah, sarjana 32 %, SMA 61,7 %, dan 78,3 %; ibu berturut-turut: sarjana 50 %, SMA 68,3 % dan SMA 73,3 %. Pekerjaan orang tua untuk ayah paling banyak swasta, berturut-turut: 70,0 %, 56,7 % dan 75,0 %. Untuk ibu paling banyak swasta, berturut-turut: 48,3%, 68,3 % dan 70,0 %. Berdasarkan sumber informasi untuk ketiga sekolah paling banyak adalah media massa, berturut-turut: 23,3 %, 26,4 % dan 27,1 %. Berdasarkan tingkat pengetahuan tentang kehamilan pada ketiga sekolah paling banyak adalah baik, berturut-turut; 70,0 %, 76,7 % dan 65,0 %. Dan sika premaja paling banyak pada ketiga sekolah adalah positif, berturut-turut: 65,0 %, 58,3 % dan 63,3 %. Dengan pengetahuan remaja yang baik tentang kehamilan remaja pada penelitian ini, menghasilkan sikap yang positif remaja untuk menghindari kehamilan pada usia remaja. Kata kunci: Remaja, kehamilan remaja, pengetahuan, sikap